Perkembangan Destinasi Alam Kapalo Banda (2012-2023) - Yora, Yora Jumadil; Fatimah, Siti (Jurnal Kronologi, 2025)
This research discusses the Kapalo Banda Nature Destination: Youth as a Destination Development Agency 2012-2023. The problems formulated are as follows: (1) how is the development of Kapalo Banda natural destination, Nagari Taram from 2012-2023, (2) how is the form of the role of youth as a natural destination development agency Kapalo Banda, in Taram Kenagarian. The purpose of this study was to determine the development of Kapalo Banda natural destinations, Nagari Taram from 2012-2023 and to determine the form of the role of youth as an agency for developing Kapalo Banda natural destinations. This research is historical research. The results of this study indicate that the development of Kapalo Banda from 2012-2023 experienced various dynamics. Starting in 2012 with the unilateral opening by youth after closing in 2010. 2014 focused on empowering members' human resources. In 2018, this destination began operating with various developments but stopped due to illegal ticket cases. In 2019, it reopened with new innovations and attracted many tourists. The Covid-19 pandemic in 2020 led to a complete closure. In 2023, Kapalo Banda reached its peak with a significant increase in the number of visitors from various regions within and outside West Sumatra.